Annotated catalogue of the Phylinae (Heteroptera: Miridae) from the Korean Peninsula - Duwal, Ram Keshari; Jung, Sunghoon; Yasunaga, Tomohide; Lee, Seunghwan (Zootaxa, 2016)
The subfamily Phylinae (Miridae) of the Korean Peninsula are catalogued. A total of 88 species are recorded from the Korean Peninsula. This catalogue is based on all available published and unpublished data, mostly representated by recent findings by Duwal in Korean region from 2010‒2015. Phylus miyamotoi Yasunaga 1999 is found for the first time from the Korean Peninsula and several species such as Atractotomus morio Sahlberg 1883, Harpocera choii Josifov 1977, H. koreana Josifov 1977, Phylus coryloides Josifov & Kerzhner 1972, and Rubrocuneocoris quercicola Josifov 1987 are newly reported from South Korea in this study. All taxa in this study are arranged according to the latest revised classification of Phylinae by Schuh & Menard (2013). Also, color image of dorsal habitus of each available species is provided.